Evaluation of Susceptibility Status of Phlebotomus papatasi, the Main Vector of Zoonotic Cutaneous Leishmaniasis, to Different WHO Recommended Insecticides in an Endemic Focus, Central Iran - Zahra Saeidi; Hassan Vatandoost; Morteza Zaim; Reza Ahmadkhaniha; Yavar Rassi; Alireza Zahraei-Ramazani; Mohammad Hossein Arandian; Reza Jafari; Yamdeu Joseph Hubert Galan; Alireza Sanei-Dehkordi; Mohammad Reza Yaghoobi-Ershadi; Amir Ahmad Akhavan (Tehran University of Medical Sciences, 2022)
Background: Among neglected zoonotic diseases, leishmaniases caused by Leishmania parasite through infected female sand fly bite, are a group of diseases found in 98 countries and territories representing a critical burden of disease worldwide. Vector management plays a crucial role in reducing the burden of vector-borne diseases by WHO's global plan. The objective of the current study was to assess the susceptibility status of wild phlebotomine sand flies from Esfahan Province, central Iran, to the recommended insecticides by WHO. Methods: Sand flies were collected by mouth aspirator in Matin Abad desert Eco-resort and were tested using WHO adult mosquito test kit against Dichlorodiphenyltrichloroethane (DDT) 4%, Deltamethrin 0.05%, Malathion 5% and Propoxur 0.1%. The number of knockdown sand flies were recorded during exposure time in ten minutes interval for DDT and Deltamethrin and they were allowed to recover for 24 hours. Knockdown Time50 (KD50) and KD90 were generated for them using Probit software. They were mounted and identified by valid keys. Results: Among the tested insecticides against female Phlebotomus papatasi, DDT, Deltamethrin, and Malathion recorded the highest mortality rate of 100%, followed by Propoxur with 92.2% mortality for a one-hour exposure. For DDT, KD50 and KD90 were calculated 21.87 and 42.93 and for Deltamethrin, they were 23.74 and 56.50 minutes respectively. Total sand flies exposed with DDT  and Deltamethrin shed their leg(s). Conclusion: It is concluded that Ph. papatasi from central Iran is susceptible to DDT, Deltamethrin, Malathion, and Propoxur.